(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The concurrent demands of vehicular electrification and thermal management present a critical engineering challenge for hybrid electric vehicles (HEVs). This paper synthesizes findings from the 2010–2020 literature to examine energy optimization strategies in HEVs alongside heat transfer enhancement techniques in microchannel heat exchangers. The analysis reveals that while fuzzy sliding mode control and neural network-based energy management systems achieve fuel economy improvements of 15-30%, the thermal densities of power control units (200-250 W/cm²) necessitate advanced cooling solutions. Microchannel heat exchangers with wavy channel configurations demonstrate heat transfer enhancements of up to 360% compared to straight channels, with single wavy-walled designs achieving 120% improvements at equivalent pumping power. Response surface methodology optimization of microchannel geometry parameters yields Pareto-optimal configurations balancing heat transfer rate (2.5-3.5 kW/kg) and pressure drop constraints. This paper establishes critical design correlations between HEV energy management and thermal optimization, providing quantitative frameworks for integrated powertrain thermal management.